2021
DOI: 10.1111/opo.12864
|View full text |Cite
|
Sign up to set email alerts
|

Does non‐strabismic amblyopia affect the quality of life of adults? Findings from a qualitative study

Abstract: Purpose While much is known about the psychosocial impacts of strabismus, little is known about the effects of non‐strabismic amblyopia on quality of life (QoL). The aim of this study was to explore the long‐term impacts of anisometropic amblyopia. Methods A phenomenological qualitative investigation was carried out on a sample of adults with anisometropic amblyopia. Subjects participated in in‐depth telephone interviews and described how their eye condition affected different aspects of their life. The interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Parents in our caregiver survey emphasised that the management of amblyopia can pose more of a burden on the child and family than the condition itself. 27,70,71 Similar to findings of previous studies, QoL implications of amblyopia typically relate specifically to its treatment, which can impact family life, social interactions or the ability to perform daily activities, as well as feelings and behaviour. 26 Consistent with our findings, Koklanis et al also found patching and glasses were associated with bullying and feelings of self-consciousness and embarrassment among children, 70 while Searle et al 71 reported that many parents also experience distress related to patching.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Parents in our caregiver survey emphasised that the management of amblyopia can pose more of a burden on the child and family than the condition itself. 27,70,71 Similar to findings of previous studies, QoL implications of amblyopia typically relate specifically to its treatment, which can impact family life, social interactions or the ability to perform daily activities, as well as feelings and behaviour. 26 Consistent with our findings, Koklanis et al also found patching and glasses were associated with bullying and feelings of self-consciousness and embarrassment among children, 70 while Searle et al 71 reported that many parents also experience distress related to patching.…”
Section: Discussionsupporting
confidence: 67%
“…[23][24][25] Furthermore, the psychosocial and emotional impact of amblyopia can affect family relationships, social interactions, career choices and mental health. [26][27][28][29][30][31] Disease in the non-amblyopic eye can also have a significant impact on earnings and economic stability, 32 with amblyopic patients reported to express feelings of fear and concern regarding the safety of their better eye. 27 While there is limited research on the effect of anisometropic amblyopia on QoL, noticeable ocular misalignment in strabismic amblyopia is associated with negative social interactions and school performance, and an increased susceptibility to psychiatric diseases and depression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is essential to reevaluate whether the influence of amblyopia on HRQoL has altered by changes in clinical practice. A previous study demonstrated that nonstrabismic amblyopia influences the quality of life of adults [ 17 ]. Currently, few studies have evaluated perspective quality of life in adolescents with nonstrabismic amblyopia.…”
Section: Introductionmentioning
confidence: 99%